The Role of Public Transportation in Sustainable Economic Growth in Jakarta Through the Concept of Transit Oriented Development (TOD) - Putranto, Panji; Maulidhika, Ika (Lafadz Jaya Publisher, 2025)
Public transportation in metropolitan cities like Jakarta has an important role in increasing economic growth. A crowded and densely populated city, of course, people's mobility is very high, so transportation is very crowded and even dense until transportation causes congestion. Public transportation in Jakarta consists of MRT (Mass Rapid Transit), LRT (Light Rail Transit), and Transjakarta buses. The high number of public transportation users in the city of Jakarta is certainly made a transit system for public transportation with the concept of Transit Oriented Development (TOD) capable of increasing sustainable economic growth such as reducing congestion, increasing the growth of business areas, operational efficiency, improving, encouraging the growth of business centers that are more crowded with potential consumers, increasing productivity and expanding job market access. This study uses a qualitative method with a literature and descriptive approach. The results of research on public transportation users in the city of Jakarta such as MRT, LRT, Transjakarta have an increase in the number of passengers from 2023 to 2025 so that it has an impact on improving the community's economy in a sustainable manner through reduced congestion, increased community mobility, efficiency in operations, especially transportation, and the economy in the TOD area.